Studies on N-(2-Thienylmethylidene)-2-aminothiophenol Complexes of Co(II), Ni(II) and Cu(II) - Spinu, Cezar; Pleniceanu, Maria; Isvoranu, Marian; Spinu, Lacramioara (Asian Journal of Chemistry, 2016)
Metal complexes ML2 and ML2Cl2, where M is Co(II), N(II), Cu(II) and L is Schiff base formed by condensation of 2-thiophenecarboxaldehyde and 2-aminothiophenol, N-(2-thienylmethylidene)-2-aminothiophenol (TNATPh), have been prepared and characterized by elemental analysis, magnetic and spectroscopic measurements. IR and NMR spectra show that the nitrogen of the azomethine group and sulphur of the thiophene ring take part in coordination in the ML2Cl2 complexes while in the ML2 compounds the ligands act as tridentate coordinating through azomethine nitrogen and both sulphur atoms. Magnetic, ESR and electronic spectral studies show a distorted octahedral structure for the ML2 and CoL2Cl2 complexes and a square-planar geometry for Ni(TNATPh)2Cl2 and Cu(TNATPh)2Cl2 complexes.